Utilization of agricultural waste in Pardomuan Motung Village, Ajibata Subdistrict, Toba Samosir Regency - Sadeli, Achmad; Ginting, Adil; Tarigan, Lina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Agriculture is the activity of utilizing biological resources carried out by humans to produce food, raw materials or energy sources, and to manage their environment. The use of biological resources included in agriculture is commonly understood by people as crop cultivation or farming (English: crop cultivation) and raising livestock (raising), even though its scope can also be in the use of microorganisms and bioenzymes in processing advanced products. Based on the analysis of the situation in Pardomuan Motung Village, the problems obtained include environmental conditions which are agricultural areas that produce a lot of waste through agricultural and livestock products caused by the lack of community knowledge about waste treatment.